Assessment of Lumbar Vertebrae Morphometry Across Different Age Groups: A Computed Tomographic Study - Neha Gaur,; Dr Satyam Khare,; Dr Shilpi Jain,; Dr Mahesh Kumar Mittal,; Dr Avinash Rastogi, (The Bioscan, 2026)
Background: Lumbar vertebral morphometry plays a critical role in spinal biomechanics, radiological interpretation, and surgical planning. Although several studies have evaluated lumbar vertebral dimensions, data on age-related morphometric changes in the Indian population remain limited. Aim: To establish age-specific morphometric standards for lumbar vertebrae (L1–L5) and to assess age-related changes using computed tomography (CT). Materials and Methods: This multicentric, cross-sectional study included 1000 CT scans of the lumbar spine from individuals aged 18–50 years. Thin-slice (1 mm) CT images were analyzed using a DICOM viewer to measure pedicle dimensions, vertebral body dimensions, canal parameters, disc-related indices, and interlaminar angles at levels L1–L5. Participants were categorized into four age groups. Statistical analysis was performed using ANOVA, with p < 0.05 considered significant. Results: Significant age-related differences were observed across most morphometric parameters at all lumbar levels (p < 0.001). Transverse dimensions, interpedicular distance, and disc parameters increased progressively from L1 to L5, while vertebral heights showed a relative decline with advancing age. The greatest remodeling was observed at L4 and L5. Conclusion: Lumbar vertebral morphometry demonstrates significant age- and level-dependent variation, with maximal structural adaptation at the lower lumbar levels. These findings provide valuable normative data for the Indian population and have important implications for radiological evaluation, implant design, and spinal surgery. Keywords Lumbar spine; Vertebral morphometry; CT scan; Age variation; Spinal biomechanics; Surgical planning